ADAPTING CYBERSECURITY RISK MANAGEMENT FOR THE QUANTUM FUTURE - Amit Awasthi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The emergence of quantum computing presents unprecedented challenges to current cybersecurity frameworks, necessitating a fundamental shift in how organizations approach cryptographic security. This article examines the implications of quantum computing advancements on existing security infrastructure, exploring the architectural vulnerabilities of current cryptographic systems and presenting a structured approach to implementing quantum-resistant solutions. This article outlines a detailed risk management strategy and implementation roadmap for organizations transitioning to quantum-safe cryptography, addressing critical aspects including cryptographic dependency mapping, governance framework evolution, and adaptive security infrastructure development. In depth review of current quantum computing capabilities and future projections, this work provides organizations with actionable guidelines for preparing their security infrastructure for the quantum era.